Genetically proxied inhibition of tumor necrosis factor and the risk of colorectal cancer: A drug-target mendelian randomization study - Chen, Min; Chen, Qian; Xiao, Xin-Yu; Feng, Si-Jia; Wang, Xiao-Ying; Tang, Tai-Chun; Zheng, Hui (Frontiers in Pharmacology, 2022)
Background Previous studies suggested that anti-TNF drugs might be repurposed as a preventive treatment for colorectal cancer. We aimed to examine whether genetically proxied inhibition of TNF receptor 1 (TNFR1) reduces the absolute risk of colorectal cancer through mendelian randomization (MR) analysis. Methods We obtained 28 single nucleotide polymorphisms (SNPs) that were located within a ±15 kilobase window of the TNFRSF1A—the gene that encodes the TNFR1 protein, and we used genetic data from three GWAS studies of circulating levels of TNFR1, C-reactive protein (CRP), and white blood counts (WBC) to screen SNPs that proxied the inhibition of TNFR1. Positive control analyses were then performed by using another three GWAS data from the ulcerative colitis cohort (n=45,975), Crohn’s disease cohort (n=40,266), and multiple sclerosis cohort (n=115,803) to confirm the effect of the included SNPs. A two-sample MR analysis was performed to examine the association between TNFR1 inhibition and the absolute risk reduction (ARR) of colorectal cancer. Results We finally included 7 SNPs to proxy the anti-TNF effect, and these SNPs caused lower levels of TNFR1, CRP, and WBC. In positive control analyses, the included SNPs caused lower odds ratio of ulcerative colitis and Crohn's disease but a higher odds ratio of multiple sclerosis, consistent with drug mechanistic actions and previous trial evidence. By using the inverse-variance weighted analyses to combine the effects of the seven SNPs, we found that the anti-TNF effect was associated with a 0.988 (95%CI 0.985 to 0.991) mg/L decrease in CRP levels and a reduction in the risk of colorectal cancer (ARR -2.1%, 95%CI -3.8% to -0.4%, p=0.01). Conclusion Our study confirmed that anti-TNF drugs were be associated with a risk reduction in colorectal cancer. Physicians could consider using anti-TNF drugs for the prevention of colorectal cancer, especially in patients with high risks of developing cancer.